Pendeteksi Suhu dan Kelembaban Ruangan Menggunakan Sensor DHT11 Berbasis Web Server - Nugroho, Adam; Wibowo, Adi; Triraharjo, Bambang (Sienna, 2024)
This article discusses the development of an Internet of Things (IoT)-based system to detect room temperature and humidity using a DHT11 sensor whose data is monitored through a web server interface. The research aims to create a real-time monitoring system with effectively integrated data. The research method includes hardware and software design, sensor data collection, and web-based interface development. The results show that this system can detect changes in temperature and humidity with a high level of accuracy and provide easy access via the web. This system has the potential to be applied in the management of indoor environments such as offices, homes, and storage rooms.